Blue Halide Perovskite Materials: Preparation, Progress, and Challenges. Issue 2 (18th December 2022) - Zhang, Kai; Cao, Long‐Xue; Tang, Yingyi; Yu, Yi; Shen, Yang; Wang, Bingfeng; Wang, Wen‐Jun; Li, Yan‐Qing; Tang, Jian‐Xin
Abstract: Halide perovskite materials are emerging as a new promising semiconductor display material owing to their excellent optical and electrical properties. Highly efficient blue perovskite light‐emitting diodes (PeLEDs) are the basis for full‐color displays and solid‐state lighting applications, but their efficiency and stability still lag far behind the red and green analogs. This review focuses on the key effect factors and novel strategies for blue emission PeLEDs. In detail, first effective strategies to obtain blue emission perovskite are discussed, and then the recent progress and strategies in blue emission PeLEDs, including the physical properties and significant improvements based on different structural perovskite materials are systematically elucidated. Finally, the main challenges relating to efficiency, stability, lead toxicity, and fabrication techniques in blue emission PeLEDs are summarized, and the promising research avenues in the future are discussed. Abstract : Halide chalcogenide light‐emitting diodes demonstrate significant advances. Significantly, the development of perovskites with 3D, 2D/quasi2D, and nanocrystals, as well as, the design of device structures, constitute the basis for creating an efficient blue emission perovskite light‐emitting diode, with further developments focusing on increasing efficiency and enhancing stability.